Comparison of fire fighting system's improvement for office and factory buildings / Aimi Syamimi Azman - Azman, Aimi Syamimi (2021)
Every countries, including Malaysia, has a building that is a source of national pride. Many buildings in Malaysia, such as KLCC, have distinctive architectural elements and a story behind their development. People may use this building for a variety of purposes, including offices and factories. These buildings, on the other hand, should be well maintained to prevent hazards from a variety of sources, such as fire. Identifying the types of fire protection commonly used in selected buildings is one of the objectives of this research. There are two types of fire protection systems, which are active and passive. This research contained details about this two fire protection systems. The next objective is related with maintenance services of fire protection systems in the buildings. When applying a system in the buildings, it need a proper services in order to maintain it functionality. This is applied to fire protection systems too, as it should be maintained and serviced well. This research involved two types of building, which are office and factory. The finding of this research is to compare the fire protection systems used in both office and factory building. The researcher collected the data through online survey that distributed to building manager of office and factory buildings. The data collected described and analyzed in order to achieve research aims and objectives. Besides, from this research, new technology of fire protection systems used in the buildings may discovered.